Efektivitas Hasil Pengelasan SMAW pada Baja ST 37 Dengan Variasi Jenis Elektroda dan Kuat Arus Terhadap Pengujian Tarik dan Korosi Bermedia Larutan H2 S0_4 - Cahya Ramadani, Pradipta Ihza; mulyaningsih, Nani; Hastuti, Sri (Universitas Muhammadiyah Metro, 2024)
To support the rapid development of industry at this time, especially in the machinery industry, it has also spurred the development of technology for making basic materials such as steel. ST 37 steel is steel produced for making various machinery components. To improve the mechanical properties of ST 37 steel, a heat treatment process is applied. To see the service life of steel, it is also necessary to pay attention to the rate of corrosion that will occur in the steel that will be used in machine components. The aim of this research is to determine the use of the right type of electrode and current strength to achieve its effective use, with the criteria that the steel has tensile strength when a tensile reaction occurs in the steel and the steel has good corrosion resistance. In this study, the electrode variations used were AWS E6010, E6013, and E7016 electrodes, with variations in current strength of 70 A, 85 A, and 110 A. The highest tensile strength values ​​during the drawing process occurred in specimens with strong AWS E7016 electrode variations. The current was 110 A. Meanwhile, the lowest tensile strength occurred in the specimen with the AWS E6013 electrode variation with a current strength of 70 A. The highest corrosion rate value occurred in the AWS E6010 electrode variation specimen with a current strength of 70 A, while the lowest corrosion rate occurred in the specimen. with AWS E7016 electrode variations with a current strength of 110 A.